2006
DOI: 10.1007/s11084-006-9020-y
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubility and the Cyanate-Mediated Synthesis of Pyrophosphate

Abstract: The justification for a less alkaline primordial ocean (than present) is briefly reviewed, along with constraints on aqueous phosphate under such conditions. Based on the assumption that CaHPO(4) dihydrate determined the availability of phosphorus species, we have carried out laboratory simulations to determine equilibrium concentrations as a function of pH (in PIPES buffer) with added NaCl and CaCl(2). Consistent with expectations, solubility declines with higher pH and [CaCl(2)], but increases only slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…We hypothesize that a proton flux, driven by the pH gradient amounting to five pH units, could translocate the orthophosphate anions from the ocean bathing the mound into the open subnanometric chambers walled by the crystal planes which tend to be oriented orthogonally to the outer and inner surface of the membrane (figures 4 and 5). For example, oxidation of ferrous hydroxide or further oxidation of green rust by nitrate towards the exterior (ocean side) of the inorganic membrane would have the effect of distorting the interlayers at their distal ends, opening them up to an influx of orthophosphate (HPO 4 22 ) from the Hadean Ocean [176], distortions that, as polarons, would migrate towards the membrane interior ( figure 5). At the same time, the proton flux might be relied upon to push these counterions down the steep proton gradient into the reduced interlayer where they would lodge, so blocking the proton flux [26].…”
Section: A Pyrophosphatase Engine: Chemiosmosis For Freementioning
confidence: 99%
“…We hypothesize that a proton flux, driven by the pH gradient amounting to five pH units, could translocate the orthophosphate anions from the ocean bathing the mound into the open subnanometric chambers walled by the crystal planes which tend to be oriented orthogonally to the outer and inner surface of the membrane (figures 4 and 5). For example, oxidation of ferrous hydroxide or further oxidation of green rust by nitrate towards the exterior (ocean side) of the inorganic membrane would have the effect of distorting the interlayers at their distal ends, opening them up to an influx of orthophosphate (HPO 4 22 ) from the Hadean Ocean [176], distortions that, as polarons, would migrate towards the membrane interior ( figure 5). At the same time, the proton flux might be relied upon to push these counterions down the steep proton gradient into the reduced interlayer where they would lodge, so blocking the proton flux [26].…”
Section: A Pyrophosphatase Engine: Chemiosmosis For Freementioning
confidence: 99%
“…Earth's oceans four billion years ago are thought to have been anoxic and mildly acidic (pH ~ 5-6 due to dissolved atmospheric CO2, NO and ephemeral SO2), rich in Fe 2+ , and also could have contained Ni 2+ , Mn 2+ , phosphates, nitrate, nitrite and some ferric and manganese ions (Macleod et al 1994;Russell and Hall 1997;Hagan et al, 2007;Martin et al 2007;Ducluzeau et al, 2009;Mloszewska et al, 2012;. The hydrothermal fluid produced by serpentinization would likely have been similar to modern-day hydrothermal fluids: alkaline, containing some silicate, trace Mo and W, and dissolved H2 and CH4 along with formate and a range of hydrocarbons (Proskurowski et al 2008;Mielke et al 2010;Lang et al 2010Lang et al , 2012Konn et al 2009;Charlou et al 2010).…”
Section: Creating a Fuel Cell Model Of A Prebiotic Hydrogeological Symentioning
confidence: 99%
“…However, the concentration of this vital element in early Earth environments and particularly in the Archaean ocean was probably higher. Phosphorous foraging was at its minimum [Konhauser et al, 2007;Planavsky et al, 2010] and high CO 2 and lower pH might have dominated oceanic chemistry [Hagan et al, 2007;Russell et al, 2010]. However, two questions about this element are central to its involvement in the emergence of life.…”
Section: Early Sources Of Energymentioning
confidence: 99%
“…Hydrogen cyanide has been proposed as an excellent prebiotic reagent for reactions leading to the synthesis of organic compounds such as amino acids, purines and pyrimidines. In addition, Hagan et al [2007] demonstrated the cyanate-mediated synthesis of pyrophosphate. There are two main scenarios where hydrogen cyanide could have been generated.…”
Section: Early Sources Of Energymentioning
confidence: 99%
See 1 more Smart Citation